AGGRESSIVENESS OF JUNIOR SCHOOLCHILDREN AS A SOCIAL AND PSYCHOLOGICAL PROBLEM - Lytvynchuk, Nataliia; Melnychenko, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article analyzes the concepts of "aggression" and "aggressiveness"; considers the psychological features of aggression in primary school children; identifies the causes of aggression in children. The factors that influence the manifestation of aggression in children are identified: family relationships and methods of education; disorders of social adaptation; disorders of school adaptation; communicative incompetence; conflict strategies of behavior; influence of the media and computer games; sex (gender) differences. The purpose of the article is to theoretically analyze and empirically study the aggressiveness of primary school children. The methods of analysis, systematization and generalization of theoretical material from scientific sources allowed us to get acquainted with domestic and foreign experience on this issue. The following methods were used in the empirical study: "Cactus" (M.A. Panfilova); "Scale of direct and indirect aggression" (K. Bierquest); questionnaire "Diagnosis of aggression" by Bass-Darkey; methodology "Hand Test" by E. Wagner, adapted by Piotrowski. Results. In the course of the study, we found that most respondents have a high level of aggressive manifestations. The consequence of this is that younger students often feel anger, anger, negativism, resentment, irritation, and distrust of the world around them. In problematic situations, they cannot cope with the desire to harm other people and use physical force. Often express negative emotions through rudeness, swearing, and threats. This creates problems in communication with parents, peers, and teachers. Conclusions. Summarizing the results of the study, it was determined that children’s aggression is one of the most acute problems of school education. The spread of aggressive forms of behavior among schoolchildren cannot but concern parents, psychologists, teachers and society as a whole. The necessity of introducing targeted preventive and psycho-corrective work of psychologists and teachers with junior schoolchildren on mastering the skills of positive communication, effective interaction with people, and the ability to find peaceful ways to resolve conflicts is substantiated